Redefining the Ideal Buttocks: A Population Analysis. Issue 6 (June 2016) - Wong, Wendy W.; Motakef, Saba; Lin, Yi; Gupta, Subhas C.
Abstract : Background: The buttocks are a key element of female beauty, with aesthetic gluteoplasty becoming one of the fastest growing plastic surgery procedures. However, there remains no clear standard for the ideal buttocks. The authors performed a population analysis of the characteristics of the ideal buttocks to guide surgical planning. Methods: Images of buttocks were digitally altered to create buttocks of varying proportions on posterior and lateral views. Waist-to-hip ratios and varying vertical proportions were studied. Data were stratified and analyzed according to age range, gender, ethnicity, and nationality of the respondents. Results: A total of 1146 responses were collected. Of 989 respondents who submitted their gluteal preferences, 482 respondents (48.7 percent) were women and 507 (51.3 percent) were men. Overall, the most attractive buttocks waist-to-hip ratio is 0.65 from the posterior view (44.2 percent of respondents). The next most attractive ratio was 0.60 (25 percent of respondents). Positioning of the lateral prominence at the inferior gluteal fold was rated by 26.3 percent of respondents as the most attractive. From the lateral view, the most attractive buttocks have a waist-to-hip ratio of 0.70 (29.8 percent of respondents), with the most prominent portion positioned at the midpoint of the buttocks (45.1 percent of respondents), which is a 50:50 vertical ratio. There were no significant differences in preferences between respondent ages, genders, or ethnicities. Conclusions: New ideal waist-to-hip ratios of 0.6 and 0.65 update the previous standards and indicate a more dramatic and "curvier" new ideal, signaling an important preference paradigm shift. The information derived from this study has the potential to guide gluteoplasty practices and techniques. Abstract : Supplemental Digital Content is available in the text.